Inequalities in health care utilization among migrants and non-migrants in Germany: a systematic review - Jens Klein; Olaf von dem Knesebeck (BMC, 2018)
Abstract Background Despite the growing number of people with migrant background in Germany, a systematic review about their utilization of health care and differences to the non-migrant population is lacking. By covering various sectors of health care and migrant populations, the review aimed at giving a general overview and identifying special areas of potential intervention. Methods A systematic review was conducted in PubMed database including records that were published until 1st of June 2017. Further criteria for eligibility were a publication in a peer-reviewed journal written in English or German language. The studies have to report quantitative and original data of a population residing in Germany. The appropriateness of the studies was judged by both authors. Studies were excluded if native controls were not originated from the same sample. Moreover, indicators of health care utilization have to assess individual behaviour like consultation or participation rates. 63 studies met the inclusion criteria for a qualitative synthesis of the findings. Results The overall findings indicate a lower utilization among migrants, although the results vary in terms of health care sector, indicator of health care utilization and migrant population. For specialist care, medication use, therapist consultations and counselling, rehabilitation as well as disease prevention (early cancer detection, prevention programs for children and oral health check-ups) a lower utilization among people with migrant background was found. The lower usage was particularly shown for migrants of the 1st generation, people with two-sided migrant background, children/adolescents and women. Due to the methodological heterogeneity a meta-analysis was not feasible. As most of the studies were cross-sectional, no causal interpretations could be drawn. Conclusions The inequalities in utilization could not substantially be explained by differences in the socioeconomic status. Other reasons of lower utilization could be due to differences in need, preferences, information, language and formal access barriers (e.g. charges, waiting times, travel distances or lost wages). Different migrant-specific and migrant-sensitive strategies are relevant to address the problem for certain health care sectors and migrant populations. Trial registration The review protocol was registered on PROSPERO (CRD42014015162).